S2.2a African histoplasmosis. (20th September 2022) - Oladele, Rita
Abstract: S2.2 Histoplasmosis and talaromycosis, September 21, 2022, 3:00 PM - 4:30 PM:    : African histoplasmosis caused by Histoplasma carpsulatum var dubosii is endemic in Africa with few cases reported from outside Africa usually attributed to travelling or visits to sub-Saharan Africa. The pathogenesis is yet unclear. Infection can be acquired via inhalation of microconidia or by direct inoculation. African histoplasmosis commonly presents with papules, nodules, ulcers, swellings, lymph node enlargement, eczematoid, or psoriosiform skin lesions. Subcutaneous abscesses may also develop with discharging sinuses containing yeast cells of the fungus. Although it is generally believed to be acquired through inhalation, the lungs are usually spared. Disseminated forms are usually characterized by the involvement of bones and other organs including the gastrointestinal tract. As a result of limited availability of diagnostics, data on its prevalence and epidemiology are scarce. As with classical histoplasmosis, African histoplasmosis also mimics other clinical entities including TB and neoplasms. More awareness and a high index of suspicion on the part of clinicians will lead to early diagnosis and invariably improve clinical outcomes. An extensive review of literature revealed 365 cases of African histoplasmosis reported globally; 236 cases from Africa and 38 cases from other geographical regions including an indigenous case report from India; the location of the remaining cases was not found, positive HIV status was found in 75 cases only. No statistically significant relationship was observed when comparing the relationship between positive HIV status and fatal outcomes ( P >.05, Fisher's exact test). A case report from the UK mentioned 21 cases of African histoplasmosis previously identified in the region and all were associated with travelling to Africa. Out of the 365 identified cases, diagnostic modality was specified in 264 cases; histopathology (87.9%, n  = 232), culture (20.8%, n  = 55), microscopy (7.2%, n  = 19), serology (2.7%, n  = 7), cytology ( n  = 1, 0.4%), polymerase chain reaction ( n  = 43, 16.3%), and peripheral blood film ( n  = 1, 0.4%). Amphotericin B ( n  = 53), itraconazole ( n  = 37), and ketoconazole ( n  = 26) were the predominant antifungals used for treatment. More studies are required to ascertain the true burden and epidemiology of African histoplasmosis and to determine whether these cases reported outside Africa were autochthonous or imported from Africa. Diagnosis by culture, although the gold standard is also not routinely achieved due to lack of biosafety level 3 cabinet especially in resource-limited settings, leading to significant under diagnosis. It is imperative that capacity building and strengthening is instituted to aid the diagnosis and management of African histoplasmosis. There is a need for more studies to ascertain whether there are additional phylogenetic species within the African clade.